Exploring the potential of gamma-irradiated chitosan as an innovative, biodegradable preservative for refrigerated Labeo rohita (Hamilton) - M. M. Towhidul Islam; Jahid M. M. Islam; Mubarak A. Khan; Hossain Uddin Shekhar (Discover Food)
Abstract Purpose Fish is a crucial source of animal protein in Bangladesh and is widely consumed across the country. Rohu fish (Labeo rohita) is particularly important due to its rapid growth and high market demand. However, the use of formalin as a preservative for Labeo rohita and other fishes in Bangladesh poses significant health risks. Methods In our study, we explored the use of gamma-irradiated chitosan as an alternative preservative to prolong the shelf life of rohu fish through microbiological, chemical, and sensory analysis. Results Untreated Labeo rohita had a refrigerated storage life of 6 days, while chitosan-treated samples at a concentration of 10 g/L showed a refrigerated storage life of 16 days, based on several spoilage parameters. Additionally, our findings revealed that 50 kGy-irradiated chitosan, even at a concentration of 1 g/L, exhibited better antimicrobial activity against gram-negative bacteria compared to other chitosan variants. Unlike formalin, which has adverse effects on human health and the environment, chitosan is non-toxic and offers various health benefits. Conclusion Thus, the results of this study demonstrate that radiation-processed chitosan has superior antimicrobial activity and serves as a safer alternative to formalin in extending the shelf life of Labeo rohita. We hope that these findings will promote the broader use of gamma-irradiated chitosan in Bangladesh and other countries to mitigate the health risks associated with formalin.